SUCCESSFUL THERAPEUTIC MANAGEMENT OF CANINE TRANSMISSIBLE VENEREAL TUMOUR IN NATIVE BREED DOGS OF TAMIL NADU - J, ARUNPANDIAN; B, NEETHU; N, SRIVASTAVA; KUJUR, ANJU; G, ASWINISIVAN (The Indian Journal of Animal Reproduction, 2021)
Canine transmissible venereal tumour (TVT) is a tumour of genital tract commonly occurring in dogs and foxes. Stray dogs act as reservoir for TVT. Incidence of TVT is higher in developing nations like India because of higher population density of stray dogs as well as due to lack of proper veterinary care in villages. The present paper places on record successful management of TVT, one in a male Chippiparai and other one in female Rajapalayam dogs belonging to Rajapalayam village of Tamil Naduwith chemotherapy using a plant alkaloid, Vincristine Sulphate at weekly intervals for 3 weeks. Both the animals recovered uneventfully.